Association Analysis of Candidate Variants in Admixed Brazilian Patients With Genetic Generalized Epilepsies - Kaibara, Felipe S.; de Araujo, Tânia K.; Araujo, Patricia A. O. R. A.; Alvim, Marina K. M.; Yasuda, Clarissa L.; Cendes, Fernando; Lopes-Cendes, Iscia; Secolin, Rodrigo (Frontiers in Genetics, 2021)
Genetic generalized epilepsies (GGE) include well-established epilepsy syndromes with generalized onset seizures: childhood absence epilepsy, juvenile myoclonic epilepsy (JME), juvenile absence epilepsy (JAE), myoclonic absence epilepsy, epilepsy with eyelid myoclonia (Jeavons syndrome), generalized tonic-clonic seizures, and generalized tonic-clonic seizures alone. Genome-wide association studies (GWAS) and exome sequencing have identified 48 single nucleotide polymorphisms (SNPs) associated with GGE. However, these studies were mainly based on non-admixed, European, and Asian populations. Thus, it remains unclear whether these results apply to patients of other origins. This study aims to evaluate whether these previous results could be replicated in a cohort of admixed Brazilian patients with GGE. We obtained SNP-array data from 87 patients with GGE, compared with 340 controls from the BIPMed public dataset. We could directly access genotypes of 17 candidate SNP, available in the SNP-array, and the remaining 31 SNPs were imputed using the BEAGLE v5.1 software. We performed an association test by logistic regression analysis, including the first five principal components as covariates. Furthermore, to expand the analysis of the candidate region, we also interrogated 14,047 SNPs which flank the candidate SNPs (1Mb). The statistical power was evaluated in terms of odds ratio and minimum allele frequency (MAF) by the genpwr package. Differences in SNP frequencies between Brazilian and Europeans, sub-Saharan African, and Native Americans were evaluated by two proportion Z-test. We identified nine flanking SNPs, located on eight candidate regions, which presented association signals which passed Bonferroni correction (rs12726617; rs9428842; rs1915992; rs1464634; rs6459526; rs2510087; rs9551042; rs9888879; and rs8133217; p-values < 3.55e-06). In addition, the two-proportion Z-test indicates that the lack of association of the remaining candidate SNPs could be due to different genomic backgrounds observed in admixed Brazilians. This is the first time that candidate SNPs for GGE are analyzed in an admixed Brazilian population, and we could successfully replicate the association signals in eight candidate regions. In addition, our results provide new insights on how we can account for population structure to improve risk stratification estimation in admixed individuals.